Examination of two artichoke cultivars under single year Hungarian climate conditions - Ombódi, Attila; Pestiné Nagy, Orsolya; Szőcs, Andrea; Dimény, Judit (Acta Agraria Debreceniensis, 2007)
Based on the results of a previous experiment, we concluded that by choosing a suitable cultivar, it is possible to produce artichoke in a one-year cultivation system in Hungarian weather circumstances. The objective of the present experiment was to investigate the performance of two Californian artichoke cultivars (Green Globe, Imperial Star) under the local conditions. Experiments were conducted in 2002 and 2003, by using fourdifferent sowing and two different planting dates (03.01. and 03.20. – planting 05.07.; 04.24. and 05.06. – planting 06.12.). For both cultivars, 100% of the plants initiated buds. In most of the cases, Imperial Star produced higher total and marketable yields than Green Globe did, while it formed bigger and more uniform buds. Our opinion is that the main reason for this result was that Imperial Star tolerated the dry and warm Hungarian summer much better. Irrespective of the variety by earlier sowing dates higher total yield was achieved. Based on our results, we found that under Hungarian circumstances, both cultivars could produce acceptable total yields. However, the weather circumstances of the given year influenced bud quality, and thus marketable yield, to a great extent.